Gender and Communication Style: Overview on Face-to-Face Communication and Online Text (Whatsapp Group) - Alvin Afif Muhtar (AL-MAIYYAH : Media Transformasi Gender dalam Paradigma Sosial Keagamaan, 2021)
This study aims to compare the styles of communication based on gender differences when communicating face-to-face and when communicating through whatsapp group media. The method used is a qualitative method with a case study approach. The data analysis used is interactive qualitative analysis, data presentation, drawing, conclusions and verification. The research subjects consisted of 10 students who were members of the whatsapp group "Blitar Student Family (KMB). The findings of this study indicate that there are differences in masculine and feminine communication styles through two communication channels. The communication style of masculin in men cannot completely be transferred to communication through virtual media, whatsapp group. Likewise for the feminine communication style, most of which are no longer maintained on virtual world communication channels. The implication of this research is that there is a change in feminine and masculine communication styles if communication done through text-based online communication media.